Bis[1,3-dihydr-oxy-2-hydroxy-methyl-2-(5-nitro-2-oxidobenzyl-ideneamino) propane-κ3 N,O,O′]zinc(II) trihydrate - Ali, Hapipah Mohd; Ng, S.W.; Basirun, Wan Jefrey; Puvaneswary, S. (International Union of Crystallography, 2007)
The Zn atom in the title compound, [Zn(C11H13N2O6)2]·3H2O, is chelated by the two terdentate Schiff base anions, resulting in a trans-ZnN2O4 octa-hedral geometry. The crystal packing is stabilized by O - H⋯O hydrogen bonds, leading to a three-dimensional network structure. © 2007 International Union of Crystallography. All rights reserved.